Kontribusi Pembelajaran Prakarya dan Kewirausahaan terhadap Minat Berwirausaha Siswa di SMA Pembagunan Laboratorium UNP - Lily Muthiah Nasution; Yusron Wikarya (LPPM Politeknik Pratama, 2023)
This research aims to determine the contribution of craft and entrepreneurship students to the entrepreneurial interest of class XI students at UNP Laboratory Development High school. The research method used is quantitative research with a correlational descriptive approach. The sampel in this study was 79 students, taken by purposive random sampeling techniques from 8 classes and 3 classes taken. The research instruments used were questionnaires and documentation instruments. Data analysis method for testing instrument validity using product moment correlation and reability testing using cronbach’s alpha. Testing data analysis requirements uses a morality test, while for hypothesis testing uses a simple segregation analiysis technique. The research results show that craft and entrepreneurship learningcontributes to students’ interest in entrepreneurship by 25.7%.